Climate hazard adaptation in Uganda’s tropical highlands: an actor-network theory perspective on gendered smallholder strategies and the role of non-state actors - Yeeko Kisira; Martin Nabaasa; Flavia Nnyanzi; Irene Josephine Nayiga (Cogent Food & Agriculture)
Climate hazards continue to worsen smallholders’ livelihoods, demanding synergy and multi-level climate adaptation strategies. While non-state actors (NSAs) increasingly support local adaptation, limited understanding exists of how gender shapes farmers’ perceptions and engagement with these actors, especially in Uganda’s highland farming communities. By applying the actor-network theory, we explored the gendered adaptation among smallholder farmers. We used a cross-sectional survey of 147 household interviews, two focus group discussions, and seven key informant interviews to collect data. Quantitative data were analyzed with descriptive statistics, Chi-square, and one-sample t-tests; qualitative data via content analysis. Men and women engage differently in adaptation: men focus more on tree planting and livestock, while women lead in crop production and marketing. Women also prefer resilient, indigenous crop varieties that are easier to manage and pest-resistant. Compared to men, women rely more on savings groups and informal networks to build social and financial capital. NSAs strengthen local adaptation through advisory services, soft loans, grants, agricultural diversification, and conservation practices. Actor-Network Theory offers a valuable lens for understanding gendered climate adaptation by highlighting the synergies between actors within structured networks. Aligning interventions with gender-specific strengths is essential for fostering inclusive, climate-resilient livelihoods and advancing global climate goals.